Spectrum of hysterosalpingographic findings among women presenting with infertility in Abuja, Nigeria’s capital - Itanyi, Ukamaka D.; Oluseyi, Hadijat O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterosalpingography HSG provides the outline of the endometrial canal and fallopian tubes and is an invaluable imaging modality in the investigative management of infertility especially in resource challenged environments. The objective of the study was to review the hysterosalpingographic (HSG) findings in women investigated for infertility in Abuja, Nigeria’s capital. Methods: This is a descriptive review of retrospective radiologic reports of 219 patients who underwent HSG as part of infertility investigation over a three-year period (2013-2015) in University of Abuja teaching Hospital. Results: A total of 219 reports were reviewed with age range of 20-53years (mean 33.9 ±5.7 2SD) years. Majority were between the ages of 26-37 years (n=102, 33.6%). Secondary infertility was the indication in 172 (78.5%) and primary infertility in 47 (21.5%). Majority of the women (n=149, 68%) had hysterosalpingographic abnormalities with Tuboperitoneal pathology as the prevalent finding in 112 (75.2%) of the cases either as a single pathology or coexisting with intrauterine abnormality. The most common endometrial cavity abnormality was uterine Fibroid seen in 53, (35.6%) women. Conclusions: Hysterosalpingography remains very important in the investigation of infertility in our center with tuboperitoneal pathology as the major contributor to female infertility.